2018
DOI: 10.25225/fozo.v67.i3-4.a1.2018
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomic signature of Eurasian eagle owl (Bubo bubo) on fish remains

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…) and even some twisting. These are comparable to fish bones collected in European Lutra lutra faeces and Bubo bubo pellets [25,26]. Similarly, the apophyses are broken but we could not observe the compaction (deformation) of the vertebrae noticed by these authors.…”
Section: Surface and Microstructuresupporting
confidence: 83%
See 1 more Smart Citation
“…) and even some twisting. These are comparable to fish bones collected in European Lutra lutra faeces and Bubo bubo pellets [25,26]. Similarly, the apophyses are broken but we could not observe the compaction (deformation) of the vertebrae noticed by these authors.…”
Section: Surface and Microstructuresupporting
confidence: 83%
“…These accumulations of dejections or regurgitation pellets can be fossilized but potential structural and chemical changes due to digestive processes are still unknown for fish bones. Only some recent works have shown the effect of digestion on the surfaces of fish bones ingested by Lutra or Bubo bubo [24,25], but these studies did not take in account the degradation of bone tissue as well as its chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that B. bubo feeds on carcasses (Serrano, 2000;Díaz-Ruiz et al, 2010;Milchev & Spassov, 2017). B. bubo is a "sitand waithunter" (Cramp & Simmons, 1985;Eriksen & Wabakken, 2018) that regurgitates some parts of its prey as pellets at the perching and nesting sites (Guillaud et al, 2018). Pellets contain some indigestible remains such as bones, furs, feathers, invertebrate parts with chitin, fish scales and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cave sites are a specific group of fish-bearing localities in terms of taphonomy since most of the fish remains in caves and rock shelters were accumulated due to the opportunistic feeding activity of owls and/or diurnal raptors (Broughton et al 2006;Russ 2010;Guillaud et al 2018;Kovalchuk et al 2020). Nad Tunelem and Bi snik caves are now located in dry valleys, whereas Krucza Skała rock shelter is positioned at a high level above the river valley.…”
Section: Palaeoenvironmental Implicationsmentioning
confidence: 99%
“…2006; Russ 2010; Guillaud et al . 2018; Kovalchuk et al . 2020).…”
Section: Palaeoenvironmental Implicationsmentioning
confidence: 99%